Sosialisasi Penggunaan SPSS dalam Meningkatkan Kompetensi Analisis Data Statistik Mahasiswa FMIPAK UNIMA - Tarigan, Yustinus; Tumanggor, Awal Mulia Rejeki; Paembonan, Tiara Lestari; Varisky Abraham Dumanaw; Jein Jeilen Tampi (Jurnal Inovasi Pengabdian Masyarakat, 2025)
SPSS (Statistical Product and Service Solution) is a statistical analysis software widely used in quantitative research. A socialization program on SPSS usage for students of the Faculty of Mathematics, Natural and Earth Sciences (FMIPAK) at Manado State University (UNIMA) aimed to enhance their understanding and skills in data processing, result interpretation, and overcoming challenges such as limited statistical uses and software access. The activity was conducted through three main stages: introduction to the SPSS interface, technical training (descriptive analysis, parametric and non-parametric tests), and consultation sessions to address specific student inquiries. Active participation indicated high enthusiasm, with evaluation results showing an improved ability to operate SPSS and interpret analytical outputs independently. Technical issues, such as internet connectivity during software downloads, provided lessons for future event preparations. This program not only supports academic tasks (e.g., thesis completion) but also equips students with analytical competencies relevant to professional settings. Training programs are necessary to strengthen mastery of modern statistical tools, ensuring students are prepared for research challenges and competitive job market demands.